The ice age - Farley, Paul, 1965. (Toronto : CNIB, 2005)
An extension of Farley's range, embracing a new and philosophical seriousness. He uncovers the evidence so often overlooked by less attentive observers, finding - in childhood games, dental records and dog-eared field guides - those details by which we are proven and elegised. 2002.
Jonathan Oliver.
Audio and text.
System requirements: IBM PC or compatible; double speed or faster CD-ROM drive; sound card and sound output device; DAISY playback software or DAISY talking book player.
Recording standard: DAISY 2.02 standard.
MP3 compression.
Compression rate: 64.
Keywords: Virus diseases -- Antarctica -- Fiction; McMurdo Station (Antarctica) -- Fiction